2013
DOI: 10.1111/bcp.12117
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate: an old bone molecule but new cardiovascular risk factor

Abstract: Phosphate handling in the body is complex and involves hormones produced by the bone, the parathyroid gland and the kidneys. Phosphate is mostly found in hydroxyapatite. however recent evidence suggests that phosphate is also a signalling molecule associated with bone formation. Phosphate balance requires careful regulation of gut and kidney phosphate transporters, SLC34 transporter family, but phosphate signalling in osteoblasts and vascular smooth muscle cells is likely mediated by the SLC20 transporter fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 175 publications
(234 reference statements)
0
14
0
Order By: Relevance
“…Multiple experiments have demonstrated that culturing VSMC in a high-phosphate medium will increase calcification in a dose-dependent manner. This is also associated with the upregulation of proteins involved in bone formation and the phenotypic differentiation seen in the VSMC (29,104). Calcification of the coronary arteries is independently associated with hyperphosphatemia in ESRD patients, and elevated serum phosphate levels, even those in the high-normal range, are correlated with a higher risk of myocardial infarction and mortality in CKD patients (53,123).…”
Section: Risk Factors For Vascular Calcification In Ckdmentioning
confidence: 99%
“…Multiple experiments have demonstrated that culturing VSMC in a high-phosphate medium will increase calcification in a dose-dependent manner. This is also associated with the upregulation of proteins involved in bone formation and the phenotypic differentiation seen in the VSMC (29,104). Calcification of the coronary arteries is independently associated with hyperphosphatemia in ESRD patients, and elevated serum phosphate levels, even those in the high-normal range, are correlated with a higher risk of myocardial infarction and mortality in CKD patients (53,123).…”
Section: Risk Factors For Vascular Calcification In Ckdmentioning
confidence: 99%
“…Increasing evidence, however, supports a role for phosphate in the pathogenesis of medial and intimal calcification. 16,17 For example, Ix et al evaluated the effect of serum phosphate on arterial calcification in patients with normal to moderate kidney function and found elevated serum levels were strongly associated with non-compressible vessels and increased ankle-brachial index after adjusting for renal function and cardiovascular risk factors. The authors suggest that increased cardiovascular events might be explained by increased arterial stiffness related to medial artery calcification.…”
Section: Discussionmentioning
confidence: 99%
“…However Cox and others developed a reproducible in vitro model using the metastatic mammary adenocarcinoma 4T1 cell line that ultimately allowed them to propose a mechanism for hydroxyapatite calcification [ 136 ]. They hypothesized that alkaline phosphatase (ALP) not only hydrolyses β-glycerophosphate to glycerol and phosphate (Pi) [ 136 ], which is similar to the initial osteoblastic differentiation process in ossification [ 142 ], but ALP also dephosphorylates OPN and hydrolyzes pyrophosphate (PPi) to Pi on the surface of mammary cells [ 143 ]. The produced Pi is then believed to be transported into the 4T1 cells by type II Na-Pi co-transporters, which have been found to be expressed in higher levels in cancer tissue as opposed to normal tissue [ 136 ].…”
Section: Vascular Calcification and Stone Formation Similarities Tmentioning
confidence: 99%